Evaluation of Curriculum Development with the CIPP Approach in the Context of Improving the Quality of Education at SMAN 1 Kelumpang Utara - Rusda, Rusda; Nasri, Nasri; Sutrisno, Sutrisno; Sulistiyana, Sulistiyana (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is grounded in the importance of curriculum development in improving the quality of education at the secondary school level. An adaptive curriculum that aligns with the needs of both students and the wider community is expected to foster the optimal achievement of educational goals. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. Data analysis followed the stages of reduction, presentation, and conclusion drawing to provide an in-depth understanding of the curriculum development process at SMAN 1 Kelumpang Utara. The findings reveal that curriculum development at SMAN 1 Kelumpang Utara has been implemented in accordance with established procedures, particularly in the aspects of planning, implementation, and evaluation. The results align with the CIPP model of curriculum evaluation, which emphasizes the integration of context, input, process, and product. Nevertheless, challenges remain, particularly the limited involvement of teachers and the community in each stage, indicating that the principle of relevance to learners’ and environmental needs has not been fully realized. Overall, the developed curriculum has contributed positively to educational quality, yet it still requires strengthened coordination, collaboration, and continuous adaptation to both national policy dynamics and local needs.